PEMBERDAYAAN MASYARAKAT TANI MELALUI KEMITRAAN DENGAN KOPERASI SUSU SAPI PERAH â€SETIA KAWANâ€ (KSPSK) DI KECAMATAN TUTUR NONGKOJAJAR PASURUAN JAWA TIMUR - Mansur, Muhammad; Mahfudz, Masyhuri (IQTISHODUNA, 2013)
ewline" Ninety-five percent of farmers in community-Nongkojajar Said District is a dairy farmer. They facethree main problems, namely the problem of animal feed, livestock population and debit illegal felling of treesdue to water over the springs. Two final problems as a result of the crisis feed. On this basis, it is necessaryhandlers serious short-term and long-term. This study aims to detect the number of problematic facing thecommunity and bring the community empowerment model farm with grass planting movement ’LOYAL’ andgrass ’LIGUM’ and evaluating program performance in depth and thorough. Methods of analysis to answerthe above purposes by using the approach Patisipatory Rural Appraisal (PRA) is a village in the understandingof participation, and Rapid Rural Appraisal (RRA) is a rapid understanding of the village. The expectedoutcome of the study is the first year; inventory of the subject matter of the feed-livestock population, inaddition to water debit inventory and socio-economic/3 others outside the principal problem. Besides, animalfeed komlifeed materialized as instant foods are made and/or purchased from the manufacturer.